2005
DOI: 10.1080/13102818.2005.10817219
|View full text |Cite
|
Sign up to set email alerts
|

Laser Light Scattering Applications in Biotechnology

Abstract: Recent advancement of laser light scattering applications in biotechnology are reviewed with emphasis on their use in the biopharmaceutical industry. Light scattering methods have been used to date to characterize biomolecules in solution. They can provide information about the size and conformation of proteins and their aggregation state as well as their ability to crystallise. In addition, modern light scattering instrumentation is becoming method of choice for studying macromolecular interactions. Interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The laser light scattering analysis can provide useful information about the size distribution and conformation of protein or protein aggregates, which has been widely used to evaluate the protein state in the solution. , Thus, the formation dynamics of EGCG-loaded apoRBFΔ E P was investigated by laser light scattering by means of fluorescence spectroscopy. Upon changing the solution pH of the EGCG-apoRBFΔ E P mixture from 4.0 to 6.7, the EGCG-loaded apoRBFΔ E P nanoparticles formed and their laser light scattering intensity was recorded in 100 min as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The laser light scattering analysis can provide useful information about the size distribution and conformation of protein or protein aggregates, which has been widely used to evaluate the protein state in the solution. , Thus, the formation dynamics of EGCG-loaded apoRBFΔ E P was investigated by laser light scattering by means of fluorescence spectroscopy. Upon changing the solution pH of the EGCG-apoRBFΔ E P mixture from 4.0 to 6.7, the EGCG-loaded apoRBFΔ E P nanoparticles formed and their laser light scattering intensity was recorded in 100 min as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the differences between the FECs and ferritin–EGCG mixtures, dynamic light scattering was performed, which is a widely applied technique to detect the hydrodynamic radius ( R H ) of the particles in a solution, and changes of relative intensity peak area on size distribution can reflect the changes in the relative amounts of different scattering objects. , The data showed that the main population of the ferritin–EGCG mixtures was centered at 79.5 nm and was rich in polymers (Figure S1), comprising about 78.5% of the total mass (Table S1), indicating that the ferritin was polymerized due to the EGCG, whereas FECs displayed an R H = 8.2 nm in size comprising 91.1% of total mass (Table S1). These results were consistent with the TEM results that the FECs were distributed homogeneously, and the aggregation extent of FECs was far lower than that of ferritin–EGCG mixtures, which exhibited a great degree of aggregation (Figure D) possibly as a result of weak bond formation such as the hydrogen bonds and hydrophobic forces …”
Section: Resultsmentioning
confidence: 99%
“…Protein association property provides important information on the catalyzing activity of the EP domains, which serves as the second ferroxidase center at high iron loading (>48 Fe 2 + /protein shell). On the other hand, laser light scattering is a widely applied technique for studying biomolecules in a solution because it can provide information about the size and conformation of proteins and their aggregation state as well as their ability to crystallize (Janmey, Hvidt, Käs, Lerche, Maggs, Sackmann, Schliwa, & Stossel, 1994;Li et al, 2009a;Pal, Elce, & Jia, 2001;Zhelev & Barudov, 2005). Therefore, protein association property was studied with these two proteins by stopped-flow experiments wherein apoferritin was rapidly mixed aerobically with a series of Fe 2 + solutions to give ratios greater than 48 Fe 2 + /shell (Fig.…”
Section: Comparison Of Protein Association Property Of Bbsf and Psfmentioning
confidence: 98%